Josephine von Knorr, eine heute fast unbekannte österreichische Dichterin - Eleonora Jeřábková (Brünner Beiträge zur Germanistik und Nordistik, 2014)
The author tries to outline a portrait of the poetess Josephine von Knorr – one of the closest friends of the renowned Austrian writer Marie von Ebner-Eschenbach. The two writers creatively influenced each other in their extensive exchange of letters. The poetry of Josephine von Knorr eventually fell into oblivion. Her poems are not only an intimate expression of her inner feelings, but also an interesting reflection of the 19th century period.